Implementation of Ship Maintenance and Equipment in Implementing Embarkation and Debarkation Passengers on KM. Tidar - Lumalan, Obet; Budiawan; Meydiansyah, M. Hamdy (Dinasti International Journal of Digital Business Management, 2025)
This study aims to evaluate the implementation of passenger embarkation and disembarkation procedures on KM. Tidar, focusing on three main aspects. First, assessing the implementation of ship safety equipment maintenance and equipment in the context of fulfilling regulatory and company requirements, and its impact on operational efficiency. Second, analyzing the implementation of inspections, reporting of non-conformities, corrective actions, and recording activities, and their impact on passenger safety and ship readiness for inspections and compliance audits to international standards. Third, evaluating the suitability of the procedures regulated in the Safety Management System (SMK) of KM. Tidar to identify, evaluate, and manage operational changes, and their impact on emergency response and adaptability to international maritime regulations. This type of research is qualitative with a descriptive approach. Data were collected through direct observation, interviews, and document analysis. The subject of the study is the passenger embarkation and disembarkation process, while the object is the implementation of Element 10 of the ISM Code related to passenger safety, operational efficiency, and compliance with international standards. The study was conducted on KM. Tidar Makassar during April-May 2024 using a non-probability sampling method to determine respondents from the relevant ship's crew. The results of the study showed that the care and maintenance of safety equipment, such as ladders, embarkation bridges, and communication devices, have improved operational efficiency and passenger safety. The process of inspection, reporting, and corrective actions are carried out systematically, supporting the ship's readiness for inspection and audit. In addition, the compliance of the Safety Management System (SMK) procedures in managing operational changes helps improve response to emergency situations and adaptability to international maritime regulations. Major obstacles such as bad weather and port congestion can be minimized through good coordination between the ship's crew and the port authority. Regular training for the crew on safety equipment is an important element in maintaining high safety standards.